PENGARUH TEKNIK RELAKSASI GENGGAM JARI TERHADAP PERUBAHANSKALA NYERI PADA PASIEN POST OPERASI SECTIO CAESAREADI RSUD PROF. DR. MARGONO SOEKARDJO PURWOKERTO - Linatu Sofiyah; Atun Raudotul Ma’rifah; Indri Heri Susanti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Sectio Caesarea is the birth of the fetus through the abdominal (laparotomy) which requires an incision into the uterus (hysterectomy). WHO estimates the number of births by sectio caesarea 10% to 15% of all birth process. Complaints perceived by sectio caesarea post-surgery patients is pain. One of the nonpharmacological treatment that can be done is a hand grip relaxation technique. The purpose of thisresearch is to know the effect of hand grip relaxation techniques to the change of pain scale in sectio caesarea post-surgery patients at Prof. Dr. Margono Soekardjo Purwokerto. Research design used in this study is quasi experiments with nonrandomized preposttest with control group. Sampling technique used is accidental sampling. The sample of the research were 32 respondent (16 respondents were as experiment groupand16 respondents were as control group). The pain scale is measured by observation sheet of numeric ratring scale. The statistical test used in this research were wilcoxon signed rank test and mann whitney u test. The result of analysis shows significant differences of pain scale after being given a hand griprelaxation technique between the experimental group and the control group with p value of 0,000 (p < α). Therefore, hand grip relaxation technique has effect to pain scale change in sectio caesarea post-surgery patients.Keywords: Hand Grip Relaxation Technique, Pain, Sectio Caesarea Post-Surgery